Cognitive sophistication and deliberation times - Carlos Alós-Ferrer; Johannes Buckenmaier (University of Zurich, Department of Economics, 2018)
Behavioral heterogeneity arising from cognitive differences among economic agents plays a fundamental role in the economy. To explain this heterogeneity, models of iterative thinking assume that certain choices indicate higher cognitive effort. That is, choices are used to infer the cognitive process behind the choices themselves. To establish this link choice data is insufficient, thus an individually-measurable correlate of cognitive effort is required. We argue that deliberation times provide this missing link. We present a simple model of heterogeneous cognitive depth, incorporating stylized facts from the psychophysical literature, which makes predictions on the relation between choices, cognitive effort, incentives, and deliberation times. In an experimental test, the predicted relations are readily observed in the data, but only when the features leading to iterative thinking are salient enough. Hence, the predicted relations become a tool to uncover the limits of models of iterative thinking.
Keywords: C72; C91; D80; D91; 330; Heterogeneity; level-k reasoning; cognitive sophistication; deliberation times; depth of reasoning; cognitive effort